Travel Post-photography for the Development of Tourism in the New Media Ecosystem - Renó, Denis Porto [UNESP]; Gobbi, Maria Cristina [UNESP]; De Morais, Osvando J. [UNESP] (Universidad de la Sabana, 2024)
The media ecosystem has been significantly transformed due to the COVID-19 pandemic between 2020 and 2022. Within these transformations, an important economic segment stands out: tourism. This transformation has been triggered by the limited mobility experienced throughout the planet. Consequently, society has begun to live new tourist experiences in virtual environments, which motivated us to carry out this project. Its methodological proposal involved the Agile Scrum procedure, commonly adopted by engineering companies, participant observation, and bibliographic research. The result was the completion of an applied research project that involves theoretical and practical procedures and gives new meaning to travel photography in the new media ecology.
Posfotografía de viaje para el desarrollo del turismo en el nuevo ecosistema mediático
A pós-fotografia de viagem para o desenvolvimento do turismo no novo ecossistema midiático
Keywords: Communication; media ecology; photography; photojournalism